Traffic light intelligent guiding control system - SHEN XIAN; MEI JUNYONG; GU QIFANG (2019)
The utility model discloses an intelligent guide control system for traffic lights. The intelligent guide control system comprises a barrier-free lane, the traffic lights and a guide unit for indicating the lowest and highest speeds per hour of a vehicle, the traffic lights are arranged at the intersections of the barrier-free lanes, and the guiding unit is arranged on a road between the two traffic lights. The traffic lights and the guide unit are in communication connection with a control unit used for calculating traffic light replacement time and indicating speed per hour by the guide unit. The number of parking times of vehicles at the intersection can be reduced, traffic jam is relieved, and energy conservation and emission reduction are achieved. 本实用新型公开了一种红绿灯智能引导控制系统，包括无障碍车道、红绿灯和用于指示车辆最低与最高时速的引导单元；所述红绿灯设置在无障碍车道的交叉处，所述引导单元设置在两红绿灯之间的道路上；所述红绿灯和引导单元均通信连接在用于计算红绿灯更替时间和引导单元指示时速的控制单元。其能够减少车辆在路口的停车次数，缓解交通拥堵，节能减排。